Burning Nation - Reedy, Trent (New York, NY : Arthur A. Levine Books, an imprint of Scholastic Inc., 2015)
Idaho is a war zone under Federal occupation, and Danny Wright and his friends in the Idaho Militia are determined to fight back, running guerrilla missions against the army--but what at first seemed like a straightforward battle against governmental repression quickly grows murky, and Danny finds that even winning the war does not mean an end to tyranny.
Keywords: Idaho -- National Guard -- Juvenile fiction; Idaho -- National Guard -- Fiction; Government, Resistance to -- Juvenile fiction; Guerrillas -- Juvenile fiction; War stories; Government, Resistance to -- Fiction; Guerrilla warfare -- Fiction; War -- Fiction; Idaho -- Juvenile fiction; Idaho -- Fiction